Coefficient estimates for a new subclass of analytic and bi-univalent functions by Hadamard product - Ebrahim Analouei Adegani; Ahmad Zireh; Mostafa Jafari (Boletim da Sociedade Paranaense de Matemática, 2020)
In this work, we introduce a new subclas of bi-univalent functions which is defined by Hadamard product and subordination in the open unit disk. and find upper bounds for the second and third coefficients for functions in this new subclass. Further, we generalize and improve some of the previously published results.